Dual allosteric modulation of pacemaker (f) channels by cAMP and voltage in rabbit SA node - DiFrancesco, Dario (Blackwell Science Inc, 1999)
1. A Monod-Whyman-Changeux (MWC) allosteric reaction model was used in the attempt to describe the dual activation of ‘pacemaker’ f-channel gating subunits by voltage hyperpolarization and cyclic nucleotides. Whole-channel kinetics were described by assuming that channels are composed of two identical subunits gated independently according to the Hodgkin-Huxley (HH) equations. 2. The simple assumption that cAMP binding favours open channels was found to readily explain induction of depolarizing voltage shifts of open probability with a sigmoidal dependence on agonist concentration. 3. Voltage shifts of open probability were measured against cAMP concentration in macropatches of sino-atrial (SA) node cells; model fitting of dose-response relations yielded dissociation constants of 0.0732 and 0.4192 μM for cAMP binding to open and closed channels, respectively. The allosteric model correctly predicted the modification of the pacemaker current (I(f)) time constant curve induced by 10 μM cAMP (13.7 mV depolarizing shift). 4. cAMP shifted deactivation more than activation rate constant curves, according to sigmoidal dose-response relations (maximal shifts of +22.3 and +13.4 mV at 10 μM cAMP, respectively); this feature was fully accounted for by allosteric interactions, and indicated that cAMP acts primarily by ‘locking’ f-channels in the open configuration. 5. These results provide an interpretation of the dual voltage- and cyclic nucleotide- dependence of f-channel activation.